Time-of-day-dependent effects of exercise on the hepatic clock and proteome in high-fat diet-fed mice - Chunxiu Huang; Xiaodan Wang; Huanghao Zhou; JingFang Zhu; Yue Hu; Huijuan Wu; Xinru Yu; Cong Chen (Journal of Physiology and Biochemistry, 2026)

Clay mineral evidence for sediment provenance and the evolution of the East Asian Winter Monsoon in the central Philippine Sea over the last 4.38 Ma - Jun Sun; Fei Guo; Huaichun Wu; Wei Huang; Jian Liu; Kai Lu; Jingfang Lu; Shuang Sun; Meinan Shi; Boya Li; Liwei Liu; Xiaoke Qiang (Global and Planetary Change, 2026)

RECA: an efficient deep learning model for the rapid identification of cotton leaf diseases - Jingfang Wang; Hongyun Song; Madineh Bijani; Longguo Wu; Laixiang Xu (Plant Biotechnology Reports, 2026)

Complex network approaches for identifying global drought teleconnection patterns - Wenliang Wang; Lei Zhou; Congcong He; Yongwen Zhang; Zhiqiang Gong; Na Ying; Panjie Qiao; Jianjun Wu; Hongquan Sun; Jingfang Fan (Global and Planetary Change, 2025)

The amino acid Ser223 acts as a key site for the binding of Thrips palmi α1 nicotinic acetylcholine receptor to neonicotinoid insecticides - Kun Zhang; Jianwen Chen; Huixiu Huang; Huiqi Wen; Jingfang Yang; Junjie Geng; Shaoying Wu (Pesticide Biochemistry and Physiology, 2025)

A global optimization method based on fuzzy clustering Kriging for aerobic wastewater treatment - Yaohui Li; Shuting Wang; Yizhong Wu; Zebin Zhang; Jingfang Shen (Journal of Environmental Management, 2025)

Dynamic characterization of volatile and non-volatile profiles during Toona sinensis microgreens growth in combination with chemometrics - Beibei Zhang; Yunhui Zhai; Zichao Wu; Cheng Wang; Jingfang Zhang (Food Research International, 2025)

Oxymatrine reduces hepatic lipid synthesis in rat model of nonalcoholic steatohepatitis by regulating Sirt1/AMPK and LXR/Plin2/SREBP-1c pathways - Jingfang Xiong; Gaofeng Chen; Ying He; Changqing Zhao; Dongya Chen; Yihui Liu; Zhaolin Zhang; Yijun Wu; Hong Xu (Chemico-Biological Interactions, 2025)

Genome-wide association mapping combined with gene-based haplotype analysis identify a novel gene for shoot length in rice (Oryza sativa L.) - Tifeng Yang; Jingfang Dong; Junliang Zhao; Longting Zhang; Lian Zhou; Wu Yang; Yamei Ma; Jian Wang; Hua Fu; Jiansong Chen; Wenhui Li; Haifei Hu; et al. (Theoretical and Applied Genetics, 2023)
Key message Genome-wide association mapping revealed a novel QTL for shoot length across multiple environments. Its causal gene, LOC_Os01g68500 , was identified firstly through gene-based haplotype analysis, gene expression and knockout transgenic verification. Abstract Strong seedling vigor is an important breeding target for rice varieties used in direct seeding. Shoot length (SL) is one of the important traits associated with seedling vigor characterized by rapid growth of seedling, which enhance seedling emergence. Therefore, mining genes for SL and conducting molecular breeding help to develop varieties for direct seeding. However, few QTLs for SL have been fine mapped or cloned so far. In this study, a genome-wide association study of SL was performed in a diverse rice collection consisting of 391 accessions in two years, using phenotypes generated by different cultivation methods according to the production practice, and a total of twenty-four QTLs for SL were identified. Among them, the novel QTL qSL-1f on chromosome 1 could be stably detected across all three cultivation methods in the whole population and indica subpopulation. Through gene-based haplotype analysis of the annotated genes within the putative region of qSL-1f , and validated by gene expression and knockout transgenic experiments, LOC_Os01g68500 (i.e., Os01g0913100 in RAP-DB) was identified as the causal gene for SL, which has a single-base variation (C-to-A transversion) in its CDS region, resulting in the significant difference in SL of rice. LOC_Os01g68500 encodes a DUF538 (Domain of unknown function) containing protein, and the function of DUF538 protein gene on rice seedling growth is firstly reported in this study. These results provide a new clue for exploring the molecular mechanism regulating SL, and promising gene source for the molecular breeding in rice.

PBX1-promoted SFRP4 transcription inhibits cell proliferation and epithelial-mesenchymal transition in endometrial carcinoma - Liwen Guo; Huihua Chen; Jinguo Chen; Chen Gao; Xianguo Fu; Sujuan Zhou; Wenjuan Wu; Taoping Li; Jingfang Lin; Tailai Yang; Zichun Chen; Luoyuan Cao (Tissue and Cell, 2023)

Streptococcus humanilactis sp.nov., isolated from healthy nursing mother's breast milk - Xiaoqing Guo; Fei Han; Lin Cong; Yu Li; Yue Wu; Chen Liu; Jingfang Yang; Risu Na; Wenjun Liu (Archives of Microbiology, 2022)

The crosstalk between the Notch, Wnt, and SHH signaling pathways in regulating the proliferation and regeneration of sensory progenitor cells in the mouse cochlea - Jingfang Wu; Wen Li; Luo Guo; Liping Zhao; Shan Sun; Huawei Li (Cell and Tissue Research, 2021)
Sensory hair cells (HCs) are highly susceptible to damage by noise, ototoxic drugs, and aging. Although HCs cannot be spontaneously regenerated in adult mammals, previous studies have shown that signaling pathways are involved in HC regeneration in the damaged mouse cochlea. Here, we used a Notch antagonist (DAPT), a Wnt agonist (QS11), and recombinant Sonic hedgehog (SHH) protein to investigate their concerted actions underlying HC regeneration in the mouse cochlea after neomycin-induced damage both in vivo and in vitro. With DAPT, the numbers of HCs increased, and supporting cell (SC) proliferation was seen in both the intact and damaged cochlear sensory epithelia, while these numbers were unchanged in the presence of QS11. When simultaneously treated with DAPT and QS11, the number of HCs increased dramatically, and much greater SC proliferation was seen in the cochlear epithelium. In transgenic mice with both Notch1 conditional knockout and β-catenin over-expression, cochlear SC proliferation and HC regeneration were more obvious than in either Notch1 knockout or β-catenin over-expressing mice separately. When cochleae were treated with DAPT, QS11, and SHH together, SC proliferation was even greater, and this proliferation was seen in both the HC region and the greater epithelial ridge. High-throughput RNA sequencing was used to identify the differentially expressed genes between all groups, and the results showed that the SHH and Wnt signaling pathways are involved in SC proliferation. Our study suggests that co-regulation of the Notch, Wnt, and SHH signaling pathways promotes extensive cell proliferation and regeneration in the mouse cochlea.

SARS-CoV-2-encoded nucleocapsid protein acts as a viral suppressor of RNA interference in cells - Jingfang Mu; Jiuyue Xu; Leike Zhang; Ting Shu; Di Wu; Muhan Huang; Yujie Ren; Xufang Li; Qing Geng; Yi Xu; Yang Qiu; Xi Zhou (Science China Life Sciences, 2020)

Evolution of the novel coronavirus from the ongoing Wuhan outbreak and modeling of its spike protein for risk of human transmission - Xintian Xu; Ping Chen; Jingfang Wang; Jiannan Feng; Hui Zhou; Xuan Li; Wu Zhong; Pei Hao (Science China Life Sciences, 2020)

TPPU, a sEH Inhibitor, Attenuates Corticosterone-Induced PC12 Cell Injury by Modulation of BDNF-TrkB Pathway - Qiong Wu; Jingfang Song; Danxin Meng; Quanzhong Chang (Journal of Molecular Neuroscience, 2019)

Effect of Change of Mechanical Ventilation Position on the Treatment of Neonatal Respiratory Failure - Jiebin Wu; Jingfang Zhai; Hongxia Jiang; Yingjun Sun; Bao Jin; Yanyan Zhang; Bin Zhou (Cell Biochemistry and Biophysics, 2015)

MicroRNA-135b regulates metastasis suppressor 1 expression and promotes migration and invasion in colorectal cancer - Weiyun Wu; Zhuang Wang; Pengchun Yang; Jingfang Yang; Jian Liang; Yuanhong Chen; Hao Wang; Guoli Wei; Shicai Ye; Yu Zhou (Molecular and Cellular Biochemistry, 2014)

A bFGF Antagonist Peptide with Anti-angiogenesis Properties in Non-small Cell Lung Cancer Cells - Ruixue Wang; Wu Luo; Xiangfeng Zeng; Jingfang Di; Yonglin Yu; Chuan Wang; Wenhui Wang; Xilei Chen; Dan He; Tao Li; Xiaoping Wu (International Journal of Peptide Research and Therapeutics, 2013)